Pengaruh Budaya Organisasi Terhadap Kinerja Karyawan Pada Maritim Muda Nusantara - Rutinaias Haholongan; Sri Handoko Sakti; Alief Muttaz Hanafi; Alvy Zahran Hidayah; Dinda Puri Melani; Rizka Fitri Amelia (Universitas Muhammadiyah Metro, 2024)
Maritim Muda Nusantara’s organizational culture is one of the factors that encouragesMaritim Muda Nusantara’s human resources to be able to perform well, by implementingcommunication as the main value of organizational culture which must be implemented wellby Maritim Muda Nusantara’s human resources as a whole. . The purpose of this research isto analyze and determine organizational culture on employee performance in the MaritimMuda Nusantara organization. This research uses qualitative methods, with interview andobservation tools, then the data during observation is selected and processed as the mostinteresting, fresh and accurate. The results of the research carried out are that there is apositive influence between organizational culture on employee performance in the MaritimMuda Nusantara organization.